Peran Emosi Dalam Proses Belajar - Isniarty Gintulangi (Journal on Education, 2024)
This study aims to analyze the role of emotions in the learning process of students. The method used in this research is a literature review. In this literature review, the data sources used are derived from academic journals, articles, and research reports published in the last 10 years, from December 2014 to December 2024. The search in this study utilized one database, Google Scholar. The search keywords used were "role of emotions", "positive emotions", "negative emotions", “the learning process” and "learners" to obtain relevant academic journals, articles, and research reports. Based on the analysis of several reading sources and previous research findings, it shows that the variable of emotion plays a crucial role in enhancing the learning process in individuals.